Metaphorical Languages in The Selected Songs from The Album Divide by Ed Sheeran - Paruntung, Yischa; Mahmud, Murni; Halim, Abdul (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
Metaphors are related to the relationship between one word and another informing a meaning. A metaphor is a word or expression than meaning is figurative rather than literal because it serves to explain a concept. The metaphor in Ed Sheeran’s song analysed by using Lakoff and Johnson (2003: 10-32), metaphor is something that has another meaning and its main function is to understand. In other words, it can be interpreted that metaphor is part of figurative language which contains comparisons of one thing with another. Qualitative method is used in this research with descriptive analysis method, which answers the research question with analyzing description. In this paper, the researcher has found that it can be showed that the dominant metaphors in Ed Sheeran's song lyrics are ontological metaphors which are more dominant than structural and orientational metaphors. The significance of the metaphors in the lyrics are generally about feelings, self, or something by replacing the word concept from the known structural metaphors with another concept. The implications of this paper are the existence of an awareness and appreciation of the metaphorical moments in daily language and also in the aspect of education.Keywords : metaphors, figurative, songs, structrual metaphor, orientational metaphor